Electron cloud buildup and instability: Numerical simulations for the CERN Proton Synchrotron - M. Giovannozzi; E. Métral; G. Métral; G. Rumolo; F. Zimmermann (Physical Review Special Topics. Accelerators and Beams, 2003)
Experimental observations on the electron cloud have been collected at the CERN Proton Synchrotron machine throughout the last two years. At the same time, an intense campaign of simulations has been carried out to understand the observed electron cloud buildup and the related instability. In this paper, the results of the numerical simulations are presented and discussed.